Impact of Frequent Use of Social Media on Human Health - Sultan Mahmood; Samana Raza; Asad Ali; Saima Batool; Fatima Bibi; Syed Muhammad Mudassir Ud Din; Kashif Ali; Swera Hafeez; Ahmad Ali; Dilawar Abbas, (Dialogue Social Science Review (DSSR), 2024)
Social media has significantly evolved in tenure of its volume, quality, and utility, in the past twenty years. Similarly, to check how essential nutrients support physical health, engaging the contents that benefit the mental well-being. Advances in technology have made this enriching content widely accessible through social media websites, which helps in conversation about mental health issues in contemporary society. Nonetheless, the beginning of the internet and social websites has directed to a shift towards virtual interactions, often resulting in feelings of being alone, which have negative consequences on intellectual and physical health. The major threat for parents, communities, and scholars is the adolescents' frequent use of social networking websites, as it has advantages and disadvantages. This study is conducted to know, how the frequent use of social sites impacts mental well-being. The results of this research indicate that younger generation of this era is the victim of mental health issues due to excessive use of social communication sites. Teenagers are a bit worried about likes and comments on their posts that they share on social media websites. It is necessary to explore the linkage between social communication websites and mental well-being because of extensive use of social sites by younger generation. Exploring the relationship between mental health and social websites is the initial step, after that we have to check that, how social sites affect the mental health of our youth.